Congestive hepatopathy secondary to large renal arteriovenous malformation - Khalife, Mohammad (BMJ Publishing Group, 2013)
A 75-year-old woman presented with acute onset dyspnoea, and was found to have signs of pulmonary congestion on clinical examination. Imaging revealed cardiomegaly and coincident congestive hepatopathy, secondary to a left renal arteriovenous malformation. The presence of a high flow vascular shunt in the left kidney was possibly the causative factor behind both the high-output cardiac failure and congestive hepatopathy.